Beyond the Minimum: A Durable Emergency Shelter - Child, Jason (University of Waterloo, 2013)
The number of states requiring humanitarian assistance after a disaster has doubled every decade since 1960. Extreme weather like flooding and violent storms associated with climate change are predicted to continue to increase with intensity and in frequency in the future. Traditionally, emergency shelters have been given in the form of two options: the tent or the tarp. While both do a great job at addressing immediate shelter needs, they are not durable enough habitations to provide adequate transitional shelter for the time period between six months and two years. Most emergency shelters provided by humanitarian agencies fail before six months. This thesis will investigate the development of an emergency shelter solution that improves upon the current options for affected regions following a disaster within warm climates. The thesis proposes that by employing more robust materials for emergency shelters the life expectancy can be extended to meet the required needs. Several materials and designs were explored, tested, and evaluated as plausible shelter solutions to accomplish this task. Design shapes including Roman and Gothic arches were tested with smoke simulations, wind load calculations, and continuous frame loading. The most successful design tested, the Roman arch, was then contrasted and compared to currently used disaster relief shelters for durability and cost. Thesis findings indicate that there is potential for economical and durable emergency shelter solutions. Further research on this topic will increase the number of shelter options available to humanitarian organizations in order to help both emergency and transitional shelter roles simultaneously.
Keywords: emergency shelter; disaster relief shelter; Architecture